Automatic inspection system for dimensional measurements of the saw blade milling cutter - Yung-Cheng Wang; Jui-Chang Lin; Shih-Fong Chiu (Journal of Industrial Engineering and Management, 2010)
The demand for measuring equipments of automatic optical inspection has grown rapidly, because of its benefits of promoted efficiency and higher precision. Instead of manual projection measurements, measurement performance and efficiency can be obviously enhanced by the image measurement system. In this investigation, digital image processing and geometrical measurement principles have been integrated to develop a dynamic measurement system for the dimensional measurements of a saw blade milling cutter. The repeatability of the measurement system has been analyzed and its accuracy has been verified by using commercial 3D image measurement system. The analysis results show that the dimensional precision of 25μm and the angular precision of 0.21° can be realized by the self-developed measurement system. Between the results of the developed system and reference standard system, there are 25μm deviation in dimensional measurement and 0.26° in angular measurement. That measuring performances can meet the industrial requirement and the higher measurement efficiency can be achieved.